Establishment of a protocol for in vitro propagation of Passiflora caerulea (Research, Society and Development, 2020)
Besides being of gastronomic and medicinal importance, Passiflora caerulea L. has been used as rootstock for commercial passion fruit, due to its resistance to phytopathogenic diseases. However, this species is susceptible to viral pathogens and presents a low germination rate. Therefore, tissue culture becomes a viable alternative for providing large-scale production, in a short period of time and free of viral diseases, being an important tool in the preservation and propagation of this species. However, there are only few studies related to the in vitro cultivation of P. caerulea, Thus, this study aimed at establishing an in vitro protocol for the species P. caerulea. using the Culture medium MS was used, with 100% and 50% concentrations of salts (MS 100% and MS 50%). To perform the experiment, the morphometry of P. caerulea seeds was initially carried out, in order to choose the seminiferous material for later germination. Then, microcuttings from plants germinated from those seeds were inoculated in medium MS 100% and MS 50%, with no addition of phytohormones. The experiment was conducted in a completely randomized design with 25 replications and the number of buds, sprout length, number of leaves, leaf color and micropile development were evaluated. The use of MS 50% showed to be feasible for the in vitro establishment of P. caerulea, without compromising the development and quality of the plants, providing cost reduction in the production of the culture medium.